Adaptive Policies in the Family Hope Program (PKH) to achieve Sustainable Development Goals in Pangkep Regency - Islamiyah, Riska; Haning, Moh. Tahir; Hidayat, Andi Rahmat (JAKPP (Jurnal Analisis Kebijakan & Pelayanan Publik), 2021)
In general, the objectives of this study are: (1) To describe how the implementation of poverty reduction policies through the Family Hope Program (PKH) in achieving the Sustainable Development Goals (SDGs) in Pangkep Regency; (2) To find out the obstacles to the implementation of poverty reduction policies through the Family Hope Program (PKH) in achieving the Sustainable Development Goals (SDGs) in Pangkep Regency. This study used a qualitative descriptive method with informants selected through the snowball technique. Data collection methods used in this study are interviews, observations, and documents related to the research. The data collected was then analyzed using the Interactive Analysis Model of Miles, Huberman & Saldana.  Based on the results of the research, the implementation of poverty reduction policies through the Family Hope Program (PKH) in Pangkep Regency concerning assisting the Adaptive Policies theory according to Swanson & Bhadwal (2009), 5 out of 7 indicators have been implemented properly to successfully achieve Goal 1 of SDGs 2030 which related to integrated and forward-looking analysis, automatic policy adjustment, decentralization of decision-making, promoting variation, and formal policy review and continuous learning. However, 2 of them have not been optimal, namely related to multistakeholder deliberation and enabling self-organization and social networking. The research found obstacles in the implementation of these policies were the lack of involvement of the private sector, geographical constraints of the region, and the mindset of the community in receiving assistance.